Characteristics Giant Cell Tumor of The Bone Cases at Dr. Mohammad Hoesin General Hospital Period 1 January 2017 - 31 Augsut 2020 - Primadika Rubiansyah; Randy Rakhmat Septiandani (HM Publisher, 2021)
Introduction : Giant Cell Tumor (GCT) is a benign bone tumors with potentially aggressive and capacity to metastasize. This tumor could destroy the bone and joint component. As a primary bone tumor that appears at productive age , GCT can cause morbidity for patients. Methods : This research is a retrospective descriptive study with data obtained from the medical records of patients who went to Mohammad Hoesin general hospital for the period January 1, 2017- August 31, 2019. Data processing was carried out using SPSS 16.0. From the research results, 27 GCT patient data that met the inclusion criteria were obtained. Results : There were 23 (85.1%) patients in the 20-44 years age group, 2 (7.4%) people <20 years, 2 (7.4%) people> 44 years. There were 13 (48%) male patients and 14 (52%) female patients. The most common tumor locations were in the proximal tibia as many as 6 (22%) people, Distal Femur as many as 6 (22%) people, Distal Radius as many as 5 (18.5%) people, Distal Ulna as many as 3 (11.1%) people, Proximal Femur as many as 1 (3.7 %) people, Calcaneus as much as 1 (3.7%) people, Metacarpal as many as 1 (3.7%) people. Based on grading Campanacci, 16 (59.25%) people had GCT with Campanacci Grade III, Grade II with 8 (29.6%) people, and 1 (3.7%) grade I. Only 2 (7.4%) people had recurrences. No patients were found to have lung metastases (0%). There were 1 (3.7%) patients with pathological fracture on GCT. Management carried out was 24 people undergoing resection and reconstruction 24 (88.5%) and 3 (11.5%) people with curettage and bone cement. Conclusion : This study of GCTB at Mohammad Hoesin general hospital bring out that patient’s characteristics are similar with other country and theory. Mostly patient got GCTB at age second until fouth decade of life, slightly more in female, mostly tumor detected around the knee. Mostly patient detected with Campanacci graded III and needed resection and reconstruction surgery. No reported lung metastases in GCTB patient but this record need further follow up due to short time between surgery and study